Compact multidimensional broadband wireless the convergence of wireless mobile and access. - Lu, W.W.
Broadband wireless communications have gained increased interest during the last few years. This has been fuelled by a large demand on high-frequency utilization as well as a large number of users requiring simultaneous high-data-rate access for the applications of wireless mobile Internet and e-commerce. The convergence of wireless mobile and access will be the next storm in wireless communications, which will use a new network architecture to deliver broadband services in a more generic configuration to wireless customers, and support value-added services and emerging interactive multimedia communications. Large bandwidth, guaranteed quality of service, and ease of deployment coupled with the great advancements in semiconductor technologies make this converged wireless system a very attractive solution for broadband service delivery.
Keywords: QoS; Broadband service delivery; Broadband services; Broadband wireless communications; Compact multidimensional broadband wireless; Converged wireless system; E-commerce.; Guaranteed quality of service; High-data-rate access; Interactive multimedia communications; Network architecture; Protocol stack; Semiconductor technologies; Value-added services; Wireless access; Wireless mobile Internet